IMPLEMENTASI PERWAKO PADANG NOMOR 14 TAHUN 2016 TENTANG PERATURAN PELAKSANAAN PERDA NOMOR 2 TAHUN 2015 TENTANG BANTUAN HUKUM UNTUK MASYARAKAT MISKIN - Mainisya Pertiwi; Aldri Frinaldi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
This research aimed to analyze the implementation Mayor Regulation of Padang Number 14 of 2016 About the Implementation of Regional Regulation Number 2 of 2015 About Legal Aid to Poor People. This was a qualitative research with normative-empiric and phenomenal approach. Informants of this research were determined with purposive sampling, that was head of subsection of legal aid and human rights of Padang City Government, Legal Aid Organizations, leaders young secretary of law Padang District Court, and poor people who received legal aid. This research used primary and secondary data derived from observation, interview, and documentation study. Validity tested of this data used source triangulation technique, and than the data were analyzed with qualitative data technique. The results of the research showed that neeed some improvement in implementation Mayor Regulation of Padang Number 14 of 2016. There are supporting factors and inhibiting factors in this regulation. Padang City Government solved the problems in this policy with some efforts.